Search for domain wall dark matter with atomic clocks on board global positioning system satellites. Issue 1 (December 2017) - Roberts, Benjamin; Blewitt, Geoffrey; Dailey, Conner; Murphy, Mac; Pospelov, Maxim; Rollings, Alex; Sherman, Jeff; Williams, Wyatt; Derevianko, Andrei
Abstract Cosmological observations indicate that dark matter makes up 85% of all matter in the universe yet its microscopic composition remains a mystery. Dark matter could arise from ultralight quantum fields that form macroscopic objects. Here we use the global positioning system as a 50, 000 km aperture dark matter detector to search for such objects in the form of domain walls. Global positioning system navigation relies on precision timing signals furnished by atomic clocks. As the Earth moves through the galactic dark matter halo, interactions with domain walls could cause a sequence of atomic clock perturbations that propagate through the satellite constellation at galactic velocities 300 km s−1 . Mining 16 years of archival data, we find no evidence for domain walls at our current sensitivity level. This improves the limits on certain quadratic scalar couplings of domain wall dark matter to standard model particles by several orders of magnitude. The composition of dark matter in the universe remains a mystery, with one hypothetical form being topological defects. Here the authors determine a stronger constraint on the coupling of this dark matter to atomic clocks on board global positioning satellites through the analysis of 16 years of archival data.